2015
DOI: 10.1080/00071668.2015.1113501
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of an exon 1 substitution in the myostatin gene and its expression in breast and leg muscle of the Bian chicken

Abstract: 1. The objective of this study was to verify the functional effects of the c.234G>A substitution in the myostatin (MSTN) gene and ascertain the mechanism by which the variant affects growth traits in the Bian chicken. 2. The c.234G>A substitution was detected by PCR-RFLP analysis in the 7th-generation Bian chickens and three genotypes (AA, AG and GG) were identified. Results showed that the substitution was significantly associated with all studied growth traits, except first-d-weight, in female Bian chickens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Our previous research showed that the c.234G > A mutation of the myostatin gene had a significant effect on the growth traits of female Bian chickens. Based on this mutation, fast-growing (AA genotype) and slow-growing (GG genotype) strains were successfully established [ 16 ]. Then, the bidirectional selection of body weight at 16 weeks was further carried out for six generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research showed that the c.234G > A mutation of the myostatin gene had a significant effect on the growth traits of female Bian chickens. Based on this mutation, fast-growing (AA genotype) and slow-growing (GG genotype) strains were successfully established [ 16 ]. Then, the bidirectional selection of body weight at 16 weeks was further carried out for six generations.…”
Section: Discussionmentioning
confidence: 99%
“…The slow- and fast-growing groups of Bian chicken were established by our team with myostatin gene-assisted selection [ 16 ]. Then, the bidirectional selection of body weight at 16 weeks was further carried out for six generations.…”
Section: Methodsmentioning
confidence: 99%
“…GO enrichment analysis showed that the KCNJ2 and GDF8 genes were in the same biological process (GO:0003012). According to existing research, these genes may be related to muscle protein production, muscle fiber diameter, muscle fiber density, and participate in muscle regulation [44,45,46]. Fernlund et al [47] found that mutations in the KCNJ2 gene may be involved in the formation of VAndersen–Tawil syndrome (ATS) syndrome, suggesting that the KCNJ2 gene has an effect on the regulation of human cardiac activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bian chicken is an eminent native Chinese breed. Zhang et al [53] established slow-growing and fast-growing groups with the gene-assisted selection for growth traits. Then the bidirectional selection of body weight at 16-week was further carried out for six generations.…”
Section: Animals and Tissuesmentioning
confidence: 99%